Reveries of the existential: a psychoanalytic observation of young children’s existential encounters at the nursery - Simopoulou, Zoi (The University of Edinburgh, 2017)
This study is an exploration of five children’s relationship with the existential as it is played out in their everydayness at the nursery. Previous research in the field has looked at teachers’ perceptions of pre-school children’s existential questions, showing, thus, a place for a study on children’s existential encounters. My focus lies with the subjective meanings and the emotional qualities of these encounters, specifically how they are embodied in children’s play in the form of a word but also an object, an image, a movement or silence as well as in their ordinary doing and their very being at the nursery. I am also interested in how the existential reveals itself in children’s everyday relationships with others as well as how it is precisely through my relationship with them that I, as someone who looks for it, can get closer to it. For that I use psychoanalytic observation as a methodology that stays with the child’s interior worlds as they unfold in her play and in the relationship with the observer. My methodology is informed by relational psychoanalytic thinking and feminist writings that allow me to locate meaning in the liminal spaces between the self and the other, the interior and the exterior. In the analysis, I use writing as inquiry as a means to explore an integrative approach by moving between psychoanalytic theories and existential-phenomenological ideas to think the existential with. I explore children’s existential encounters with the questions of nothingness, strangeness, ontological insecurity, death and selfhood as they emerged in the context of our relationship in the course of the observations. I also discuss how time, space and relationship - as inherent in the existential but also implicated in the method of psychanalytic observation - manifested in children’s existential encounters. Finally, I look at the idea of the interpersonal unconscious as a creative source of meaning and discuss how the existential emerged embodied in symbolic articulations in the form of character, imagery, sounds and scents.
Keywords: existential; psychoanalytic observations; children; writing as inquiry